SEGMENTATION AND COMPACT MULTISCALE REPRESENTATION OF THE IMAGES BASED ON PROGRESSIVE BACKWARD CLUSTERING - O. M. Almiahi; V. Yu. Tsviatkou; E. G. Makeichik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Developing a method of segmentation and compact multiscale representation of images based on the progressive backward clustering. The method provides an accurate segmentation, multiscale representation and compression of the segmented images, adaptation to a limitation on the time of segmentation.